Influence of Gallic Acid and Thai Culinary Essential Oils on Antibacterial Activity of Nisin against Streptococcus mutans - Pimsumon Jiamboonsri; Pimpikar Kanchanadumkerng (Advances in Pharmacological and Pharmaceutical Sciences)
Streptococcus mutans is a well-known oral pathogen commonly associated with a normal dental problem and life-threatening infection. A bacteriocin nisin and the plant-derived compounds including gallic acid (GA) and Thai culinary essential oils (EOs) have been reported to have activity against oral pathogens. However, their synergistic interaction against S. mutans has not been explored. The purposes of this study were primarily to investigate anti-S. mutans properties and the antibiofilm formation of nisin, GA, and five EOs by using the broth microdilution method. Besides, the morphological change, killing rate, and antibacterial synergism were determined by scanning electron microscopy (SEM), time-kill assay, and checkerboard method, respectively. The results demonstrated that kaffir lime leaf (KLL) oil, lemongrass (LG) oil, and GA showed a potent anti-S. mutans activity and inhibited biofilm formation with the possible mechanism targeted on the cell membrane. Additionally, KLL oil revealed anti-S. mutans synergism with GA, LG oil, and chlorhexidine with the fractional inhibitory concentration (FIC) indexes ≤ 0.5. Interestingly, GA displayed a high potential to enhance anti-S. mutans activity of nisin by lowering the minimum inhibitory concentrations (MICs) to at least 8-fold in a bacteriostatic manner. These results suggest that GA and KLL oil may be potentially used as an adjunctive therapy along with nisin and chlorhexidine to control S. mutans infection.